High-crystallinity superfine nickel powder and preparation method thereof
By regulating the nickel nucleation process in the aqueous phase using ultrasonic waves and combining with the heat treatment of molten salts, high crystallinity ultrafine nickel powder was prepared, which solved the problems of uneven particle size and low crystallinity in the prior art, and achieved better oxidation resistance and heat shrinkage resistance.
Patent Information
- Application Number
- CN202510212819.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-02-25
AI Technical Summary
The existing ultrafine nickel powder preparation methods have problems such as uneven particle size, low crystallinity and high cost. Especially when preparing nano-grade nickel powder, technical difficulty is high and the powder is prone to sticking into chain shapes.
By adjusting the nickel nucleation process using ultrasonic waves in the aqueous phase, combined with heat treatment of molten salt, high crystallinity ultrafine nickel powder with uniform particle size and spherical shape is prepared.
The obtained high-crystalline ultrafine nickel powder has better oxidation resistance and heat shrinkage resistance, and is suitable for conductive paste, metal electrode materials, magnetic shielding materials and other fields, overcoming the problems of uneven particle size and low crystallinity in traditional methods.
Smart Images

Figure CN119870445A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of electronic materials and metal powder materials, and specifically relates to a high-crystallinity ultrafine nickel powder and a preparation method thereof, and more specifically to a method for obtaining a high-crystallinity ultrafine nickel powder by using ultrasound to adjust the generated size of the nickel powder in a liquid phase and combining it with molten salt heat treatment. Background Art
[0002] Ultrafine nickel powder is widely used in conductive slurries, catalytic and magnetic materials due to its excellent electrical conductivity, catalytic properties and magnetic properties. The preparation methods of ultrafine nickel powder mainly include physical methods and chemical methods. The physical method is to prepare nickel powder by physical methods such as mechanical grinding and evaporation-condensation. This method is relatively simple and environmentally friendly, but it has high requirements on equipment and high energy consumption, and the size of the prepared nickel powder is often not uniform. The chemical method generally prepares nickel powder by reduction, mainly including chemical vapor deposition (CVD), sol-gel method, microemulsion method, liquid phase reduction method and hydrothermal method.
[0003] For example, Chinese invention patent CN116525320A discloses a method for preparing nickel particles, in which nickel chloride powder, methanol and zirconium oxide balls are placed in a planetary ball mill for grinding, and then filled with argon and then filled with high-temperature hydrogen to reduce nickel chloride to nickel powder with an average particle size of 200 to 700 nm. This method requires hydrogen reduction, and the size of the prepared nickel particles is relatively large. Chinese invention patent CN118086951A discloses a method for preparing uniform and stable nickel nanoparticles on a silicon substrate, in which nickel sulfate hexahydrate, L-histidine and boric acid are prepared as an electroplating solution, and nickel ions complexed with L-histidine are precipitated and reduced to nickel nanoparticles by constant potential deposition, with an average particle size of 15-18 nm, and then loaded on a silicon substrate. Chinese invention patent CN102133644A discloses a method for preparing nickel nanoparticles, in which nickel nitrate, ethanolamine and polyvinyl pyrrolidone are dissolved in ethanol respectively, and then heated to 66°C in an oil bath to obtain nickel nanoparticles with an average particle size of 10 nm. This method requires the use of organic solvents, and due to the low reaction temperature, the crystallinity of the nickel particles is not high enough.
[0004] From the reported literature, the preparation of ultrafine nickel powder mainly has the following problems. First, the size of nickel powder prepared by CVD method is generally above 200 nanometers. The preparation of nickel powder of smaller size has the disadvantages of high technical difficulty, high cost and uneven powder size. Physical vapor deposition (PVD) method also has the disadvantages of easy adhesion of nickel powder into chains and poor particle size uniformity in the preparation of ultrafine nickel powder, especially nano-level nickel powder. In the chemical liquid phase preparation method of nickel powder, the organic liquid phase method has a high cost due to the use of oil-soluble organic solvents. Although the aqueous phase reduction method can easily obtain nickel powder with particle size ranging from tens of nanometers to hundreds of nanometers, uniform size and approximately spherical shape, the crystallinity of the powder is poor due to the low reaction temperature (room temperature to 100°C). Single nickel particles are often secondary structures formed by the agglomeration of multiple smaller nickel original particles, and the smoothness of the particle surface is also poor, which is not conducive to application. Summary of the invention
[0005] The present invention aims to provide a method for producing ultrafine nickel powder with high crystallinity in view of the above problems. The method uses ultrasound to regulate the nucleation process of nickel in the aqueous phase, so as to obtain small-sized original nickel powder, and further combines the heat treatment of molten salt to finally obtain ultrafine nickel powder with high crystallinity and uniform size and spherical shape, with a size of 100 to 200 nanometers. Compared with the ultrafine nickel powder prepared by the conventional aqueous phase reduction method, the nickel powder prepared by the present invention has better oxidation resistance and heat shrinkage resistance, and can be applied to many fields such as conductive slurry, metal electrode material, magnetic shielding material, etc.
[0006] The present invention adopts the following technical solution:
[0007] A method for preparing ultrafine nickel powder with high crystallinity comprises the following steps:
[0008] (1) Weighing a certain amount of nickel precursor and dissolving it in deionized water, then adding hydrazine hydrate and stirring evenly, which is referred to as solution A; obtaining an alkaline aqueous solution, which is referred to as solution B;
[0009] (2) mixing the solution B and the solution A and subjecting them to ultrasonic treatment;
[0010] (3) After the ultrasonic treatment, the reaction solution is stirred, and after a period of reaction, the reaction product is separated by magnetic separation, and then washed and dried to obtain nickel powder;
[0011] (4) mixing the nickel powder and the combined salt, heating the mixture, introducing a protective gas, keeping the mixture warm for a period of time, and then cooling the mixture; the combined salt comprises a binary mixed salt of at least two different chloride salts;
[0012] (5) washing, magnetically separating and drying the product obtained in step (4) to obtain ultrafine nickel powder with high crystallinity.
[0013] In a specific embodiment, the following steps may be adopted:
[0014] (1) Weigh a certain amount of nickel precursor and dissolve it in deionized water, then add a certain proportion of hydrazine hydrate and stir evenly, which is recorded as solution A; weigh a certain amount of sodium hydroxide and dissolve it in deionized water, which is recorded as solution B.
[0015] Preferably, the nickel precursor is selected from at least one of nickel acetate, nickel sulfate and nickel chloride. The concentration of the nickel precursor is 0.04-1.60 mol / L; the molar ratio of hydrazine hydrate to the nickel precursor is 3:1-15:1. The concentration of solution B is 20-75 mol / L.
[0016] (2) Solution B is added to solution A in a certain proportion (relative to solution A), and before adding solution B, an ultrasonic oscillator is turned on and ultrasonicated for a period of time at a certain ultrasonic power.
[0017] Preferably, the volume ratio of solution B to solution A is 1:1 to 10:1, more preferably 1:4 to 10:1.
[0018] Preferably, the ultrasonic power is 20-200W, preferably 40-150W, more preferably 50-100W.
[0019] Preferably, the ultrasonic time is 0 to 60 minutes, more preferably 1 to 15 minutes.
[0020] (3) Turn off the ultrasonic machine, react the reaction solution at a certain stirring rate for a period of time, separate the reaction product with a magnet, wash the reaction product with deionized water and ethanol, and dry it to obtain ultrafine nickel powder.
[0021] Preferably, the stirring rate is 50 to 600 rpm, more preferably 100 to 300 rpm; the reaction time is 5 minutes to 2 hours, more preferably 30 minutes to 2 hours.
[0022] (4) The prepared ultrafine nickel powder and a specific combined salt are mixed in a certain proportion by a mixer and then loaded into a crucible, and the crucible is placed in a tubular furnace, a protective gas is introduced, heated to a certain temperature, kept warm for a period of time, and naturally cooled to room temperature.
[0023] Preferably, the combined salt is selected from at least one of AlCl3-NaCl, AlCl3-MgCl2, AlCl3-KCl, AlCl3-CaCl2, AlCl3-LiCl, FeCl3-NaCl, and ZnCl2-KCl binary mixed salt systems.
[0024] Preferably, the ratio of the combined salt is: the molar ratio of AlCl3 to NaCl is 1:0.1 to 1:0.7; the molar ratio of AlCl3 to MgCl2 is 1:0.1 to 1:0.5; the molar ratio of AlCl3 to KCl is 1:0.1 to 1:0.7; the molar ratio of AlCl3 to CaCl2 is 1:0.1 to 1:0.5; the molar ratio of AlCl3 to LiCl is 1:0.1 to 1:0.8; the molar ratio of FeCl3 to NaCl is 1:0.1 to 1:0.4; the molar ratio of ZnCl2-KCl is 1:0.1 to 1:0.6.
[0025] Preferably, the ratio of the ultrafine nickel powder to the combined salt is 1:1 to 1:10, and more preferably 1:3 to 1:7.
[0026] Preferably, the heating temperature is 300-650°C, more preferably 350-550°C;
[0027] Preferably, the protective atmosphere is selected from one of argon, nitrogen, argon-hydrogen mixed gas, and nitrogen-hydrogen mixed gas, and more preferably argon or nitrogen.
[0028] Preferably, the insulation time is 0.1 to 5 hours.
[0029] (5) The product obtained in step (4) is washed once with a certain concentration of dilute acid, washed several times with deionized water and ethanol water, separated with a magnet, and dried to finally obtain a high-crystallinity ultrafine nickel powder with a particle size in the range of 100 to 200 nanometers.
[0030] Preferably, the dilute acid is any one of hydrochloric acid, sulfuric acid, nitric acid and acetic acid, and the concentration is 0.1-1 mol / L.
[0031] The present invention also protects the high crystallinity ultrafine nickel powder prepared by the method for preparing the high crystallinity ultrafine nickel powder, which has at least one of the following (1) to (4):
[0032] (1) The particle size of the highly crystalline ultrafine nickel powder is 100 to 200 nanometers and is uniform in size;
[0033] (2) The temperature at which the high-crystallinity ultrafine nickel powder begins to oxidize when heated in air is greater than or equal to 300° C.;
[0034] (3) Compared with the nickel powder obtained in step (3), the high-crystallinity ultrafine nickel powder has a sharper diffraction peak and a higher degree of crystallinity due to the molten salt treatment in step (4);
[0035] (4) The high crystallinity ultrafine nickel powder is made into a slurry and coated on a ceramic substrate to form a thin film, which has anti-heat shrinkage performance.
[0036] The present invention also protects the application of the high-crystallinity ultrafine nickel powder in conductive materials, catalytic materials or magnetic shielding materials.
[0037] Furthermore, the conductive material is a conductive paste, a metal electrode or a ceramic capacitor.
[0038] Beneficial effects:
[0039] The present invention uses nickel salt as a precursor, hydrazine hydrate as a reducing agent, and water as a solvent to react in an ultrasonic field. By adjusting the power of the ultrasonic machine, an ultrafine nickel powder with an adjustable particle size within 100 to 200 nm is prepared. Compared with other methods for controlling the size of metal particles, ultrasonic technology can effectively control the particle growth stage, making it difficult for the reduced nickel crystal nuclei to agglomerate to form larger particles, which is conducive to obtaining a smaller nickel powder product and reducing the generation of by-products; different ultrasonic powers are conducive to obtaining an adjustable size to meet more nickel powder application requirements. In addition, using water as a reaction solvent has the advantages of environmental protection, low toxicity, and low cost compared to using organic solvents.
[0040] Secondly, placing ultrafine nickel powder in molten salt (i.e., combined salt) for heat treatment is a novel method to improve the crystallinity of its particles. Molten salt has molten ionic liquid in the reaction process, which can effectively isolate the particles from merging with each other. The spatial confinement effect of molten salt can ensure the high dispersion of particles. At the same time, due to the strong polarization force provided by anions and cations in the molten salt, the diffusion of nickel atoms in a high temperature environment is restricted, and it is difficult for particles to connect and fuse with each other. Therefore, after heat treatment with molten salt at an appropriate temperature, the size and morphology of the initially synthesized nickel particles can be basically maintained, and high crystallinity is also obtained. The binary mixed salt system described in the present invention can provide a molten liquid phase with a suitable temperature for nickel particles to improve their crystallinity. In addition, after heat treatment with molten salt, the oxidation resistance and heat shrinkage resistance of nickel particles are greatly improved. In the application of multilayer ceramic capacitors (MLCC), due to the large difference in thermal expansion coefficients between ultrafine nickel powder and dielectric ceramic materials, serious stratification and cracks will occur in the subsequent sintering process, causing discontinuity problems in the nickel electrode layer. The high crystallinity ultrafine nickel powder prepared by the present invention is conducive to obtaining a continuous and less defective nickel electrode layer due to its improved crystallinity and heat shrinkage resistance, which is of great significance for manufacturing high-capacity ultra-thin layer capacitors. In the field of magnetic shielding materials, high crystallinity also increases the saturation magnetization of nickel, especially nano-scale nickel powder, which is beneficial for its magnetic shielding effect.
[0041] Finally, the common CVD method has the disadvantages of difficult preparation technology, high cost, and uneven powder size when preparing nickel powder with a size of about 100 nanometers, while the PVD method also has the disadvantages of easy adhesion of nickel powder particles and uneven size. The present invention uses the regulating effect of ultrasonic action to obtain ultrafine nickel powder with a particle size as low as 100 nanometers and relatively uniform size, and also obtains high crystallinity, antioxidant performance and heat shrinkage resistance, overcoming the disadvantage that the nickel powder prepared by conventional aqueous phase reduction has good size uniformity but lacks high crystallinity. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a scanning electron microscope photograph of the ultrafine nickel powder prepared in Example 1, with a scale of 200 nm.
[0043] Figure 2 This is the XRD pattern of the ultrafine nickel powder prepared in Example 1.
[0044] Figure 3 This is a scanning electron microscope photograph of the ultrafine nickel powder prepared in Example 2, with a scale of 200 nm.
[0045] Figure 4 This is the XRD pattern of the ultrafine nickel powder prepared in Example 2.
[0046] Figure 5 This is the TG curve of the ultrafine nickel powder prepared in Example 2.
[0047] Figure 6 This is a scanning electron microscope photograph of the ultrafine nickel powder prepared in Example 3, with a scale of 200 nm.
[0048] Figure 7 This is the XRD pattern of the ultrafine nickel powder prepared in Example 3.
[0049] Figure 8 This is a scanning electron microscope photograph of the ultrafine nickel powder prepared in Example 4, with a scale of 200 nm.
[0050] Fig. 9 This is a scanning electron microscope photograph of the ultrafine nickel powder prepared in Example 5, with a scale of 200 nm.
[0051] Fig.10 This is the XRD pattern of the ultrafine nickel powder prepared in Example 5.
[0052] Fig.11 This is a scanning electron microscope photograph of the ultrafine nickel powder prepared in Example 6, with a scale of 200 nm.
[0053] Fig.12 This is the XRD pattern of the ultrafine nickel powder prepared in Example 6.
[0054] Fig.13This is a scanning electron microscope photograph of the ultrafine nickel powder prepared in Example 7, with a scale of 200 nm.
[0055] Fig.14 This is a scanning electron microscope photograph of the ultrafine nickel powder prepared in Example 8, with a scale of 200 nm.
[0056] Fig.15 This is a scanning electron microscope image of the ultrafine nickel powder prepared in Example 9, with a scale of 200 nm.
[0057] Fig.16 This is the XRD pattern of the ultrafine nickel powder prepared in Example 9.
[0058] Fig.17 This is a scanning electron microscope image of the ultrafine nickel powder prepared in Example 10, with a scale of 200 nm.
[0059] Fig.18 This is the XRD pattern of the ultrafine nickel powder prepared in Example 10.
[0060] Fig.19 This is a scanning electron microscope image of the ultrafine nickel powder prepared in Example 11, with a scale of 200 nm.
[0061] Fig. 20 This is the XRD pattern of the ultrafine nickel powder prepared in Example 11.
[0062] Fig.21 This is a scanning electron microscope photograph of the ultrafine nickel powder prepared in Comparative Example 1, with a scale of 200 nm.
[0063] Fig. 22 This is the XRD pattern of the ultrafine nickel powder prepared in Comparative Example 1.
[0064] Fig.23 This is the TG curve of the ultrafine nickel powder prepared in Comparative Example 1.
[0065] Fig.24 This is a scanning electron microscope photograph of the ultrafine nickel powder prepared in Comparative Example 2, with a scale of 1 μm.
[0066] Fig.25 This is a scanning electron microscope photograph of the ultrafine nickel powder prepared in Comparative Example 3, with a scale of 10 μm.
[0067] Fig.26 This is a scanning electron microscope photograph of the ultrafine nickel powder prepared in Comparative Example 4, with a scale of 10 μm. DETAILED DESCRIPTION
[0068] The embodiments of the present invention are described in detail below. The examples of the embodiments are intended to explain the present invention and should not be construed as limiting the present invention. If no specific techniques or conditions are specified in the embodiments, the techniques or conditions described in the literature in the art or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially. % is not explicitly stated as mass percentage.
[0069] Example 1
[0070] (1) 65 mL of nickel acetate tetrahydrate aqueous solution (0.73 mol / L) and 36 mL of hydrazine hydrate were uniformly mixed and recorded as solution A. 24 mL of sodium hydroxide aqueous solution (25 mol / L) was prepared and recorded as solution B. Solution B was added to solution A, and the ultrasonic machine was not turned on (i.e., the ultrasonic power was zero), and the reaction was carried out at a stirring rate of 250 rpm for 1 hour. The product was washed three times with deionized water and once with ethanol, and the product was separated with a magnet and dried in a vacuum drying oven at 80°C for 4 hours to obtain ultrafine nickel powder to be further processed.
[0071] (2) 2 g of the ultrafine nickel powder prepared in step (1) was mechanically mixed with 10.31 g of aluminum chloride hexahydrate and 1.47 g of sodium chloride, and then loaded into a crucible. The crucible was placed in a tube furnace, sealed, and the heating device was turned on. Argon was introduced and the temperature was raised to 400° C. and kept warm for 2 hours. After naturally cooling to room temperature, the mixture was washed with dilute hydrochloric acid, deionized water, and ethanol, respectively. The product was separated by a magnet and dried in a vacuum drying oven at 80° C. for 4 hours to obtain a high-crystallinity ultrafine nickel powder.
[0072] Figure 1 This is a scanning electron microscope photograph of the product. The particles are spherical and the average particle size is about 180nm.
[0073] Figure 2 is the XRD pattern of the product, which is different from the XRD pattern of the product of Comparative Example 1 (not treated in step (2)) ( Fig. 22 ), the diffraction peak is obviously sharper, indicating that the product has a higher degree of crystallinity.
[0074] Example 2
[0075] (1) 65 mL of nickel acetate tetrahydrate aqueous solution (0.73 mol / L) and 36 mL of hydrazine hydrate were uniformly mixed and recorded as solution A. 24 mL of sodium hydroxide aqueous solution (25 mol / L) was prepared and recorded as solution B. Solution B was added to solution A, and the ultrasonic machine was not turned on (i.e., the ultrasonic power was zero), and the reaction was carried out at a stirring rate of 250 rpm for 1 hour. The product was washed three times with deionized water and once with ethanol, and the product was separated with a magnet and dried in a vacuum drying oven at 80°C for 4 hours to obtain ultrafine nickel powder to be further processed.
[0076] (2) 2 g of the ultrafine nickel powder prepared in step (1) was mechanically mixed with 10.31 g of aluminum chloride hexahydrate and 1.47 g of sodium chloride, and then loaded into a crucible. The crucible was placed in a tube furnace, sealed, the heating device was turned on, and argon was introduced. The temperature was raised to 500°C and kept warm for 2 hours. After naturally cooling to room temperature, the mixture was washed once with dilute hydrochloric acid, twice with deionized water, and once with ethanol. The product was separated by a magnet and placed in a vacuum drying oven at 80°C for 4 hours to obtain a highly crystalline ultrafine nickel powder.
[0077] Figure 3 This is a scanning electron microscope photograph of the product. The particles are spherical and have a smoother surface than those in Example 1.
[0078] Figure 4 is the XRD pattern of the product, which is different from the XRD pattern of the product of Comparative Example 1 (not treated in step (2)) ( Fig. 22 ), the diffraction peak is obviously sharper, indicating that the product has a higher degree of crystallinity.
[0079] Figure 5 The thermogravimetric analysis (TG) graph of the product shows that the temperature at which the high-crystallinity ultrafine nickel powder begins to oxidize in air is about 300°C. Compared with the TG result of the product of Comparative Example 1 (not treated in step (2)), Fig.23 ) compared with the original.
[0080] Example 3
[0081] (1) 65 mL of nickel acetate tetrahydrate aqueous solution (0.73 mol / L) and 36 mL of hydrazine hydrate were uniformly mixed and recorded as solution A. 24 mL of sodium hydroxide aqueous solution (25 mol / L) was prepared and recorded as solution B. Solution B was added to solution A, and the ultrasonic cleaning machine was not turned on (i.e., the ultrasonic power was zero), and the reaction was carried out at a stirring rate of 250 rpm for 1 hour. The product was washed three times with deionized water and once with ethanol, and the product was separated with a magnet and dried in a vacuum drying oven at 80°C for 4 hours to obtain ultrafine nickel powder to be further processed.
[0082] (2) 2 g of the ultrafine nickel powder prepared in step (1) was mechanically mixed with 10.31 g of aluminum chloride hexahydrate and 1.47 g of sodium chloride, and then loaded into a crucible. The crucible was placed in a tube furnace, sealed, the heating device was turned on, and argon was introduced. The temperature was raised to 550°C and kept warm for 2 hours. After naturally cooling to room temperature, the mixture was washed once with dilute hydrochloric acid, twice with deionized water, and once with ethanol. The product was separated by a magnet and dried in a vacuum drying oven at 80°C for 4 hours to obtain ultrafine nickel powder with high crystallinity.
[0083] Figure 6 The scanning electron microscope photograph of the product shows that the particles are still spherical and their dispersibility is similar to that of the product in Example 2.
[0084] Figure 7 is the XRD pattern of the product, which is different from the XRD pattern of the product in Comparative Example 1 ( Fig. 22 ), the diffraction peaks are sharper, indicating that the product has a higher degree of crystallinity.
[0085] Example 4
[0086] (1) 65 mL of nickel acetate tetrahydrate aqueous solution (0.73 mol / L) and 36 mL of hydrazine hydrate were uniformly mixed and recorded as solution A. 24 mL of sodium hydroxide aqueous solution (25 mol / L) was prepared and recorded as solution B. Solution B was added to solution A, and the ultrasonic machine was not turned on (i.e., the ultrasonic power was zero), and the reaction was carried out at a stirring rate of 250 rpm for 1 hour. The product was washed three times with deionized water and once with ethanol, and the product was separated with a magnet and dried in a vacuum drying oven at 80°C for 4 hours to obtain ultrafine nickel powder to be further processed.
[0087] (2) 2 g of the ultrafine nickel powder prepared in step (1) was mechanically mixed with 13.58 g of aluminum chloride hexahydrate and 1.10 g of magnesium chloride, and then loaded into a crucible. The crucible was placed in a tube furnace, sealed, the heating device was turned on, and argon was introduced. The temperature was raised to 500°C and kept warm for 2 hours. After naturally cooling to room temperature, the mixture was washed once with dilute hydrochloric acid, twice with deionized water, and once with ethanol. The product was separated by a magnet and placed in a vacuum drying oven at 80°C for 4 hours to obtain a highly crystalline ultrafine nickel powder.
[0088] Figure 8 The scanning electron microscope photograph of the product shows that the particle surface becomes smoother than that of Comparative Example 1.
[0089] Example 5
[0090] (1) 65 mL of nickel acetate tetrahydrate aqueous solution (0.73 mol / L) and 36 mL of hydrazine hydrate were uniformly mixed and recorded as solution A. 24 mL of sodium hydroxide aqueous solution (25 mol / L) was prepared and recorded as solution B. Solution B was added to solution A, and the ultrasonic machine was turned on within 10 seconds before adding solution B, the power was set to 100% of the rated power (100 W), the ultrasonic time was 3 minutes, and the reaction was carried out at a stirring rate of 250 rpm for 1 hour. Wash with deionized water three times and ethanol once, separate the product with a magnet, and place it in a vacuum drying oven at 80°C for 4 hours to obtain ultrafine nickel powder to be further processed.
[0091] (2) 2 g of the ultrafine nickel powder prepared in step (1) was mechanically mixed with 10.31 g of aluminum chloride hexahydrate and 1.47 g of sodium chloride, and then loaded into a crucible. The crucible was placed in a tube furnace, sealed, the heating device was turned on, and argon was introduced. The temperature was raised to 500°C and kept warm for 2 hours. After naturally cooling to room temperature, the mixture was washed once with dilute hydrochloric acid, twice with deionized water, and once with ethanol. The product was separated by a magnet and placed in a vacuum drying oven at 80°C for 4 hours to obtain a highly crystalline ultrafine nickel powder.
[0092] Fig. 9 The scanning electron microscope photo of the product has a particle size of about 100-110 nm. Compared with Examples 1, 2, 3 and Comparative Example 1, the particle size is smaller, showing the regulating effect of ultrasound on the particle size of nickel powder.
[0093] Fig.10 is the XRD pattern of the product, which is different from the XRD pattern of the product of Comparative Example 1 (not treated in step (2)) ( Fig. 22 ), the diffraction peak is obviously sharper, indicating that the product has a higher degree of crystallinity.
[0094] Example 6
[0095] (1) 65 mL of nickel acetate tetrahydrate aqueous solution (0.73 mol / L) and 36 mL of hydrazine hydrate were uniformly mixed and recorded as solution A. 24 mL of sodium hydroxide aqueous solution (25 mol / L) was prepared and recorded as solution B. Solution B was added to solution A, and the ultrasonic machine was turned on within 10 seconds before adding solution B, the power was set to 100% of the rated power (100 W), the ultrasonic time was 3 minutes, and the reaction was carried out at a stirring rate of 250 rpm for 1 hour. Wash with deionized water three times and ethanol once, separate the product with a magnet, and place it in a vacuum drying oven at 80°C for 4 hours to obtain ultrafine nickel powder to be further processed.
[0096] (2) 2 g of the ultrafine nickel powder prepared in step (1) was mechanically mixed with 10.31 g of aluminum chloride hexahydrate and 1.47 g of sodium chloride, and then loaded into a crucible. The crucible was placed in a tube furnace, sealed, the heating device was turned on, and argon was introduced. The temperature was raised to 400°C and kept warm for 2 hours. After naturally cooling to room temperature, the mixture was washed once with dilute hydrochloric acid, twice with deionized water, and once with ethanol. The product was separated by a magnet and placed in a vacuum drying oven at 80°C for 4 hours to obtain a highly crystalline ultrafine nickel powder.
[0097] Fig.11 The scanning electron microscope photo of the product shows that the particle size is about 100 nm. Compared with Examples 1, 2, 3 and Comparative Example 1, the particle size is smaller, which shows the regulating effect of ultrasound on the particle size of nickel powder.
[0098] Fig.12is the XRD pattern of the product, which is different from the XRD pattern of the product of Comparative Example 1 (not treated in step (2)) ( Fig. 22 ), the diffraction peak is obviously sharper, indicating that the product has a higher degree of crystallinity.
[0099] Example 7
[0100] (1) 65 mL of nickel acetate tetrahydrate aqueous solution (0.73 mol / L) and 36 mL of hydrazine hydrate were uniformly mixed and recorded as solution A. 24 mL of sodium hydroxide aqueous solution (25 mol / L) was prepared and recorded as solution B. Solution B was added to solution A, and the ultrasonic machine was turned on within 10 seconds before adding solution B, the power was set to 70% of the rated power (100 W), the ultrasonic time was 3 minutes, and the reaction was carried out at a stirring rate of 250 rpm for 1 hour. Wash with deionized water three times and ethanol once, separate the product with a magnet, and place it in a vacuum drying oven at 80°C for 4 hours to obtain ultrafine nickel powder to be further processed.
[0101] (2) 2 g of the ultrafine nickel powder prepared in step (1) was mechanically mixed with 10.31 g of aluminum chloride hexahydrate and 1.47 g of sodium chloride, and then loaded into a crucible. The crucible was placed in a tube furnace, sealed, the heating device was turned on, and argon was introduced. The temperature was raised to 500°C and kept warm for 2 hours. After naturally cooling to room temperature, the mixture was washed once with dilute hydrochloric acid, twice with deionized water, and once with ethanol. The product was separated by a magnet and placed in a vacuum drying oven at 80°C for 4 hours to obtain a highly crystalline ultrafine nickel powder.
[0102] Fig.13 The scanning electron microscope photo of the product shows that the particle size is about 130 nm. Compared with Examples 1, 2, 3 and Comparative Example 1, the particle size is smaller, which shows the regulating effect of ultrasound on the particle size of nickel powder.
[0103] Example 8
[0104] (1) 65 mL of nickel acetate tetrahydrate aqueous solution (0.73 mol / L) and 36 mL of hydrazine hydrate were uniformly mixed and recorded as solution A. 24 mL of sodium hydroxide aqueous solution (25 mol / L) was prepared and recorded as solution B. Solution B was added to solution A, and the ultrasonic machine was turned on within 10 seconds before adding solution B, the power was set to 40% of the rated power (100 W), the ultrasonic time was 3 minutes, and the reaction was carried out at a stirring rate of 250 rpm for 1 hour. The product was washed three times with deionized water and once with ethanol, and the product was separated with a magnet and placed in a vacuum drying oven at 80°C for 4 hours to obtain ultrafine nickel powder to be further processed.
[0105] (2) 2 g of the ultrafine nickel powder prepared in step (1) was mechanically mixed with 10.31 g of aluminum chloride hexahydrate and 1.47 g of sodium chloride, and then loaded into a crucible. The crucible was placed in a tube furnace, sealed, the heating device was turned on, and argon was introduced. The temperature was raised to 500°C and kept warm for 2 hours. After naturally cooling to room temperature, the mixture was washed once with dilute hydrochloric acid, twice with deionized water, and once with ethanol. The product was separated by a magnet and placed in a vacuum drying oven at 80°C for 4 hours to obtain a highly crystalline ultrafine nickel powder.
[0106] Fig.14 The scanning electron microscope photo of the product shows that the particle size is about 150 nm. Compared with Examples 1, 2, 3 and Comparative Example 1, the particle size is smaller, which shows the regulating effect of ultrasound on the particle size of nickel powder.
[0107] Example 9
[0108] (1) 65 mL of nickel sulfate aqueous solution (0.73 mol / L) and 40 mL of hydrazine hydrate were uniformly mixed, which was recorded as solution A. 30 mL of sodium hydroxide aqueous solution (25 mol / L) was prepared, which was recorded as solution B. Solution B was added to solution A, and the ultrasonic machine was turned on within 10 seconds before adding solution B, the power was set to 75% of the rated power (200 W), the ultrasonic time was 3 minutes, and the reaction was carried out at a stirring rate of 300 rpm for 1 hour. Wash with deionized water three times and ethanol once, separate the product with a magnet, and place it in a vacuum drying oven at 80°C for 4 hours to obtain ultrafine nickel powder to be further processed.
[0109] (2) The ultrafine nickel powder prepared in step (1) is mechanically mixed with the combined salt of aluminum chloride hexahydrate and calcium chloride and then loaded into a crucible, wherein the molar ratio of AlCl3 to CaCl2 is 1:0.1, and the mass ratio of the nickel powder to the combined salt is 1:5. The crucible is placed in a tube furnace, sealed, the heating device is turned on, and argon is introduced. The temperature is raised to 400°C and kept warm for 2 hours. After naturally cooling to room temperature, it is washed once with dilute hydrochloric acid, washed twice with deionized water, and washed once with ethanol. The product is separated by a magnet and placed in a vacuum drying oven at 80°C for 4 hours to obtain a high-crystallinity ultrafine nickel powder.
[0110] Fig.15 The scanning electron microscope photo of the product shows that the particle size is about 150 nm. Compared with Examples 1, 2, 3 and Comparative Example 1, the particle size is smaller, which shows the regulating effect of ultrasound on the particle size of nickel powder.
[0111] Fig.16 is the XRD pattern of the product, which is different from the XRD pattern of the product of Comparative Example 1 (not treated in step (2)) ( Fig. 22 ), the diffraction peak is obviously sharper, indicating that the product has a higher degree of crystallinity.
[0112] Example 10
[0113] (1) 65 mL of nickel chloride aqueous solution (0.73 mol / L) and 50 mL of hydrazine hydrate were uniformly mixed and recorded as solution A. 35 mL of sodium hydroxide aqueous solution (25 mol / L) was prepared and recorded as solution B. Solution B was added to solution A, and the ultrasonic machine was turned on within 10 seconds before adding solution B, the power was set to 60% of the rated power (200 W), the ultrasonic time was 3 minutes, and the reaction was carried out at a stirring rate of 400 rpm for 1 hour. Wash with deionized water three times and ethanol once, separate the product with a magnet, and place it in a vacuum drying oven at 80°C for 4 hours to obtain ultrafine nickel powder to be further processed.
[0114] (2) The ultrafine nickel powder prepared in step (1) is mechanically mixed with the combined salt of zinc chloride and potassium chloride and then loaded into a crucible, wherein the molar ratio of zinc chloride to potassium chloride is 1:0.3, and the mass ratio of nickel powder to the combined salt is 1:3. The crucible is placed in a tube furnace, sealed, the heating device is turned on, and argon is introduced. The temperature is raised to 400°C and kept warm for 2 hours. After naturally cooling to room temperature, it is washed once with dilute sulfuric acid (concentration of 0.5 mol / L), washed twice with deionized water, and washed once with ethanol. The product is separated by a magnet and placed in a vacuum drying oven at 80°C for 4 hours to obtain a high-crystallinity ultrafine nickel powder.
[0115] Fig.17 The scanning electron microscope photo of the product shows that the particle size is about 140 nm. Compared with Examples 1, 2, 3 and Comparative Example 1, the particle size is smaller, which shows the regulating effect of ultrasound on the particle size of nickel powder.
[0116] Fig.18 is the XRD pattern of the product, which is different from the XRD pattern of the product of Comparative Example 1 (not treated in step (2)) ( Fig. 22 ), the diffraction peak is obviously sharper, indicating that the product has a higher degree of crystallinity.
[0117] Embodiment 11
[0118] (1) 65 mL of nickel acetate tetrahydrate aqueous solution (0.73 mol / L) and 45 mL of hydrazine hydrate were uniformly mixed and recorded as solution A. 24 mL of potassium hydroxide aqueous solution (30 mol / L) was prepared and recorded as solution B. Solution B was added to solution A, and the ultrasonic machine was turned on within 10 seconds before adding solution B, the power was set to 100% of the rated power (200 W), the ultrasonic time was 3 minutes, and the reaction was carried out at a stirring rate of 500 rpm for 1 hour. Wash with deionized water three times and ethanol once, separate the product with a magnet, and place it in a vacuum drying oven at 80°C for 4 hours to obtain ultrafine nickel powder to be further processed.
[0119] (2) Mechanically mix 2 g of the ultrafine nickel powder prepared in step (1) with the combined salt of ferric chloride and sodium chloride, and then put them into a crucible, wherein the molar ratio of ferric chloride to sodium chloride is 1:0.3, and the mass ratio of nickel powder to the combined salt is 1:8. The crucible is placed in a tube furnace, sealed, the heating device is turned on, and argon is introduced. Heat to 400°C and keep warm for 2 hours. After naturally cooling to room temperature, wash once with dilute hydrochloric acid (concentration of 0.5 mol / L), wash twice with deionized water, wash once with ethanol, separate the product with a magnet, and place it in a vacuum drying oven at 80°C and dry for 4 hours to obtain ultrafine nickel powder with high crystallinity.
[0120] Fig.19 The scanning electron microscope photo of the product shows that the particle size is about 120 nm. Compared with Examples 1, 2, 3 and Comparative Example 1, the particle size is smaller, indicating the regulating effect of ultrasound on the particle size of nickel powder.
[0121] Fig. 20 is the XRD pattern of the product, which is different from the XRD pattern of the product of Comparative Example 1 (not treated in step (2)) ( Fig. 22 ), the diffraction peak is obviously sharper, indicating that the product has a higher degree of crystallinity.
[0122] Comparative Example 1
[0123] (1) 65 mL of nickel acetate tetrahydrate aqueous solution (0.73 mol / L) and 36 mL of hydrazine hydrate were uniformly mixed and recorded as solution A. 24 mL of sodium hydroxide aqueous solution (25 mol / L) was prepared and recorded as solution B. Solution B was added to solution A, and the reaction was carried out at a stirring rate of 250 rpm for 1 hour without turning on the ultrasonic cleaning machine. The product was washed three times with deionized water and once with ethanol. The product was separated with a magnet and dried in a vacuum drying oven at 80°C for 4 hours to obtain ultrafine nickel powder.
[0124] Fig.21 The scanning electron microscope photograph shows that the particle size is about 180nm and the particle surface is relatively rough.
[0125] Fig. 22 As shown in its XRD diagram, its diffraction peak is obviously broader than that of Examples 1 to 11, indicating that without heat treatment of the combined salt, the crystallinity of the nickel powder is relatively low.
[0126] Fig.23 TG diagram of the product, from which it can be seen that the initial oxidation temperature of the nickel powder in the air is about 250°C, which is lower than the initial oxidation temperature of the nickel powder prepared in Examples 1 to 11, showing poor antioxidant performance.
[0127] Comparative Example 2
[0128] (1) 65 mL of nickel acetate tetrahydrate aqueous solution (0.73 mol / L) and 36 mL of hydrazine hydrate were uniformly mixed and recorded as solution A. 24 mL of sodium hydroxide aqueous solution (25 mol / L) was prepared and recorded as solution B. Solution B was added to solution A, and the ultrasonic machine was turned on within 10 seconds before adding solution B, the power was set to 40% of the rated power (100 W), the ultrasonic time was 3 minutes, and the reaction was carried out at a stirring rate of 250 rpm for 1 hour. The product was washed three times with deionized water and once with ethanol, and the product was separated with a magnet and placed in a vacuum drying oven at 80°C for 4 hours to obtain ultrafine nickel powder to be further processed.
[0129] Weigh 2g of the above ultrafine nickel powder into a crucible, place the crucible in a tube furnace, seal it, turn on the heating device, and introduce argon. The heat treatment temperature is 550°C and the holding time is 2 hours. After cooling naturally to room temperature, the product is obtained.
[0130] Fig.24 The scanning electron microscope photo of the product shows that the spherical morphology is destroyed and some particles are fused and sintered. This shows that if the treatment method of step (2) of the embodiment is not adopted (refer to Examples 1 to 11), the nickel powder particles will not be able to maintain the initial state of synthesis, which is not conducive to subsequent applications.
[0131] Comparative Example 3
[0132] The ultrafine nickel powder prepared in Comparative Example 1 was added to a mixed solution containing 50 vol% of ethylene glycol and 50 vol% of ethylene glycol methyl ether, and prepared into a slurry with a solid content of 60 wt% by ultrasound and stirring. The slurry was coated into a thin film on a ceramic substrate and then calcined at 1200°C for 1 hour in a 5% (volume ratio) hydrogen-argon mixed atmosphere to form a conductive film.
[0133] Fig.25 This is a scanning electron microscope photograph of the sintered film of nickel powder prepared in Comparative Example 1. It can be seen that the surface of the film has shrunk severely and a large area of disconnected areas has appeared.
[0134] Comparative Example 4
[0135] The ultrafine nickel powder prepared in Example 3 was added to a mixed solution containing 50 vol% of ethylene glycol and 50 vol% of ethylene glycol methyl ether, and prepared into a slurry with a solid content of 60 wt% by ultrasound and stirring. The slurry was coated into a thin film on a ceramic substrate and then calcined at 1200°C for 1 hour in a 5% (volume ratio) hydrogen-argon mixed atmosphere to form a conductive film.
[0136] Fig.26 The scanning electron microscope photograph of the prepared nickel sintered film shows that, compared with Comparative Example 3, the shrinkage degree of the film surface is smaller and the connected area is larger, showing better anti-heat shrinkage performance.
[0137] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.
Claims
1. A method for preparing ultrafine nickel powder with high crystallinity, characterized in that: The following steps are involved: (1) Weigh a certain amount of nickel precursor and dissolve it in deionized water, then add hydrazine hydrate and stir evenly, which is recorded as solution A; An alkaline aqueous solution is obtained, which is referred to as solution B; (2) mixing the solution B and the solution A and subjecting them to ultrasonic treatment; (3) After the ultrasonic treatment, the reaction solution is stirred, and after a period of reaction, the reaction product is separated by magnetic separation, and then washed and dried to obtain nickel powder; (4) mixing the nickel powder and the combined salt, heating the mixture, introducing a protective gas, keeping the mixture warm for a period of time, and then cooling the mixture; the combined salt comprises a binary mixed salt of at least two different chloride salts; (5) washing, magnetically separating and drying the product obtained in step (4) to obtain ultrafine nickel powder with high crystallinity.
2. The method for preparing high crystallinity ultrafine nickel powder according to claim 1, characterized in that: In step (1), the nickel precursor is selected from at least one of nickel acetate, nickel sulfate and nickel chloride; the concentration of the solution obtained by dissolving the nickel precursor in deionized water is 0.04-1.60 mol / L; the molar ratio of hydrazine hydrate to the nickel precursor is 3:1-15:1; the concentration of hydroxide in the solution B is 20-75 mol / L; the volume ratio of the solution B to the solution A is 1:1-5:
1.
3. The method for preparing high crystallinity ultrafine nickel powder according to claim 2, characterized in that: In step (2), the power of the ultrasonic treatment is 20 to 200 W, preferably 40 to 150 W, more preferably 50 to 100 W; the time of the ultrasonic treatment is 0 to 60 minutes, preferably 1 to 30 minutes, more preferably 1 to 15 minutes; Preferably, in step (3), the stirring rate is 50 to 600 rpm, preferably 100 to 300 rpm; the reaction time is 5 minutes to 2 hours, preferably 30 minutes to 2 hours.
4. The method for preparing high crystallinity ultrafine nickel powder according to any one of claims 1 to 3, characterized in that: In step (4), the combined salt is selected from at least one of AlCl3-NaCl, AlCl3-MgCl2, AlCl3-KCl, AlCl3-CaCl2, AlCl3-LiCl, FeCl3-NaCl, and ZnCl2-KCl binary mixed salt systems.
5. The method for preparing high crystallinity ultrafine nickel powder according to claim 4, characterized in that: In step (4), the ratio of the combined salt is: the molar ratio of AlCl3 to NaCl is 1:0.1 to 1:0.7; or the molar ratio of AlCl3 to MgCl2 is 1:0.1 to 1:0.5; or the molar ratio of AlCl3 to KCl is 1:0.1 to 1:0.7; or the molar ratio of AlCl3 to CaCl2 is 1:0.1 to 1:0.5; or the molar ratio of AlCl3 to LiCl is 1:0.1 to 1:0.8; or the molar ratio of FeCl3 to NaCl is 1:0.1 to 1:0.4; or the molar ratio of ZnCl2-KCl is 1:0.1 to 1:0.
6.
6. The method for preparing high crystallinity ultrafine nickel powder according to claim 4, characterized in that: In step (4), the mass ratio of the nickel powder to the combined salt is 1:1 to 1:10, preferably 1:1 to 1:8, and more preferably 1:1 to 1:
5.
7. The method for preparing high crystallinity ultrafine nickel powder according to claim 6, characterized in that: In step (4), the temperature of the heating treatment is 300 to 650° C., preferably 400 to 600° C., and more preferably 500 to 550° C.; the protective gas is selected from argon, nitrogen, argon-hydrogen mixed gas, and nitrogen-hydrogen mixed gas; and the insulation reaction time is 0.1 to 5 hours; Preferably, in step (5), the washing comprises: washing once with dilute acid, and washing several times with deionized water and ethanol water, wherein the dilute acid is any one of hydrochloric acid, sulfuric acid, nitric acid and acetic acid, and the concentration is 0.1 to 1 mol / L.
8. The high crystallinity ultrafine nickel powder prepared by the method for preparing high crystallinity ultrafine nickel powder according to any one of claims 1 to 7 is characterized in that: Having at least one of the following (1) to (4): (1) The particle size of the highly crystalline ultrafine nickel powder is 100 to 200 nanometers and is uniform in size; (2) The temperature at which the high-crystallinity ultrafine nickel powder begins to oxidize when heated in air is greater than or equal to 300° C.; (3) The high-crystallinity ultrafine nickel powder has a sharper diffraction peak and a higher degree of crystallinity than the nickel powder obtained in step (3); (4) The high crystallinity ultrafine nickel powder is made into a slurry and coated on a ceramic substrate to form a thin film, which has anti-heat shrinkage performance.
9. Use of the highly crystalline ultrafine nickel powder according to claim 8 in conductive materials, catalytic materials or magnetic shielding materials.
10. The use according to claim 9, characterized in that: The conductive material is conductive paste, metal electrode or ceramic capacitor.
Citation Information
Patent Citations
Method for preparing nickel nano particles
CN102133644A
Preparation method of MLCC small-particle-size nickel particles
CN116525320A
Method for preparing uniform and stable nickel nanoparticle catalyst on silicon substrate
CN118086951A
Ultrasonic assisted method for preparing precursor of ternary positive material of lithium ion battery
CN103482711A
Preparation method of superfine nickel powder
CN103722178A
Cited By
Preparation method of superfine nickel powder
CN120901275A
Method for preparing high-purity nickel through carbonylation of nickel chloride
CN121447056A
A method for preparing high-purity nickel by carbonylation of nickel chloride
CN121447056B